Kevalidan Media Pembelajaran Berbasis Powtoon Pada Materi Himpunan di Kelas VII SMP Negeri 1 Remboken - Syintha Wangka,; Victor R. Sulangi,; Derel F. Kaunang, (Student Scientific Creativity Journal, 2023)
The availability of learning media that can stimulate interest and student learning outcomes is very important in learning. The purpose of this research was to find out the Development of Powtoon-Based Learning Media in Sets. This research was conducted at SMP Negeri 1 Remboken. The type of research used is research and development or Research and Development. The resulting media prototype was developed using the modified ADDIE development model (analysis, design, development, implementation, and development). The research results obtained from developing powtoon-based learning media in the set are expressed by an average validation score of 4.19 by media experts and 4.6 by material experts. This learning media meets valid criteria and can be used in learning.